2007
DOI: 10.1080/08830180701365917
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory CD4+CD25+T-cells are Controlled by Multiple Pathways at Multiple Levels

Abstract: CD4(+)CD25(+) regulatory T-cells (Treg cells) are an important subset of T-cells that functions to negatively control immune responses to self or non-self antigens. Depletion of CD4(+)CD25(+) Treg cells leads to the occurrence of lymphoproliferative autoimmune diseases in animals and humans. Therefore, CD4(+)CD25(+) Treg cells must be tightly regulated in the physiologic situation. In this article, we try to summarize the regulating pathways of the development, survival, and function of CD4(+)CD25(+) Treg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 82 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Recently, researchers have investigated whether depletion of a subset of T lymphocytes called regulatory T lymphocytes (Tregs) can potentiate immunotherapies against cancer. Tregs are a subpopulation of CD4 + T lymphocytes that constitutively express the transcription factor Foxp3, the high affinity IL2 receptor CD25 and the B7 ligand CTLA4 [20]. Tregs are required for the maintenance of tolerance throughout the lifetime of the organism [21] and mutations in Foxp3 are known to cause acute autoimmune disorders in humans [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have investigated whether depletion of a subset of T lymphocytes called regulatory T lymphocytes (Tregs) can potentiate immunotherapies against cancer. Tregs are a subpopulation of CD4 + T lymphocytes that constitutively express the transcription factor Foxp3, the high affinity IL2 receptor CD25 and the B7 ligand CTLA4 [20]. Tregs are required for the maintenance of tolerance throughout the lifetime of the organism [21] and mutations in Foxp3 are known to cause acute autoimmune disorders in humans [22].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, Miura reported that alloantigen stimulation significantly upregulated expression of CD134 and FoxP3 on CD4 lymphocytes [ 34 ]. CD134 was shown to regulate Treg function since administration of CD134 antibody abrogated suppression mediated by Tregs in a GvHD model, in addition to its participation in development and homeostasis of Tregs [ 35 ]. Expression of CD278 was shown to define subsets of Tregs with differences in cytokine production [ 36 ], as well as viability and suppressive capability [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Immunosuppressive CD4 + CD25 + Foxp3 + Treg cells play crucial roles in the maintenance of self-immune tolerance and keep host proper intensity of immune response (Qu and Zhao 2007;. Decreased numbers and/or functional deficiency of CD4 + CD25 + Foxp3 + Treg cells result in development of a variety of autoimmune diseases like multiple sclerosis and type I diabetes (Wang et al 2006;Zeng et al 2012;Miyara et al 2014).…”
Section: Mmg Exposure On Cd4 + Cd25 + Treg Cellsmentioning
confidence: 99%